Transmission and generation investment in electricity markets: The effects of market splitting and network fee regimes - Veronika Grimm; Alexander Martin; Martin Weibenzahl; Gregor Zoettl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2014)
In this paper we propose a three-level computational equilibrium model that allows to analyze the impact of the regulatory environment on transmission line expansion (by the regulator) and investment in generation capacity (by private firms) in liberalized electricity markets. The basic model analyzes investment decisions of the transmission operator (TO) and private firms in expectation of an energy only market and cost-based redispatch. In different specifications we consider the cases of one versus two price zones (market splitting) and analyze different approaches to recover network cost, in particular lump sum, capacity based, and energy based fees. In order to compare the outcomes of our multi-stage market model with the first best benchmark, we also solve the corresponding integrated planer problem. In two simple test networks we illustrate that energy only markets can lead to suboptimal locational decisions for generation capacity and thus, imply excessive network expansion. Market splitting heals those problems only partially. Those results obtain for both, capacity and energy based network tariffs, although investment slightly differs across those regimes.
Keywords: 330; Electricity markets; Network Expansion; Generation Expansion; Investment Incentives; Computational Equilibrium Models; Transmission Management